A Study on The Use Soybean Varietes and Addition of Eggs in The Preparation and Storage of Egg Tofu) - Rohaman, M. Maman; Enie, A. Basrah; -, Hanafi; Syarief, Rizal (Balai Besar Industri Agro, 1994)
The aim of this experiment was to study the effect of soybean varieties (Glycine max var. Tidar and var. Galunggung) and the addition of eggs (0,2,4 and 6%)on egg tofu quality. The addition of egg before soymilk boiling gave the best result in which the protein content of the whey in the lowest.The product were analysed after 0,4 and 8 days of storage and was still in good condition after 8 days at 10-15 degree C.Phycal, chemical,microbiological and panel tset showed that the best result was obtained using tidar variety and less than 2 percent addition of egg.Â